Feasibility of monitoring patient based health outcomes in a routine hospital setting. Issue 3 (September 1995) - Ruta, D; Coutts, A; Abdalla, M; Masson, J; Russell, E; Brunt, P; McKinlay, A; Mowat, A; Sinclair, T
Abstract : OBJECTIVE--To assess the feasibility of monitoring health outcomes in a routine hospital setting and the value of feedback of outcomes data to clinicians by using the SF 36 health survey questionnaire. DESIGN--Administration of the questionnaire at baseline and three months, with analysis and interpretation of health status data after adjustments for sociodemographic variables and in conjunction with clinical data. Exploration of usefulness of outcomes data to clinicians through feedback discussion sessions and by an evaluation questionnaire. SETTING--One gastroenterology outpatient department in Aberdeen Royal Hospitals Trust, Scotland. PATIENTS--All (573) patients attending the department during one month (April 1993). MAIN MEASURES--Ability to obtain patient based outcomes data and requisite clinical information and feed it back to the clinicians in a useful and accessible form. RESULTS--Questionnaires were completed by 542 (95%) patients at baseline and 450 (87%) patients at follow up. Baseline health status data and health outcomes data for the eight different aspects of health were analysed for individual patients, key groups of patients, and the total recruited patient population. Significant differences were shown between patients and the general population and between different groups of patients, and in health status over time. After adjustment for differences in sociodemography and main diagnosis patients with particularly poor scores were identified and discussed. Clinicians judged that this type of assessment could be useful for individual patients if the results were available at the time of consultation or for a well defined group of patients if used as part of a clinical trial. CONCLUSIONS--Monitoring routine outcomes is feasible and instruments to achieve this, such as the SF 36 questionnaire, have potential value in an outpatient setting. IMPLICATIONS--If data on outcomes are to provide a basis for clinical and managerial decision making, information systems will be required to collect, analyse, interpret, and feed it back regularly and in good time.